2018
DOI: 10.21776/ub.afssaae.2018.001.02.2
|View full text |Cite
|
Sign up to set email alerts
|

Application of microwave assisted extraction in extracting Torbangun leaves (Coleus ambonicus, L.) and its effects on polyphenol and flavonoids content

Abstract: Flavonoids Microwave Assisted Extraction Polyphenols Torbangun Leaves Torbangun leaves (Coleus ambonicus, L.) contain polyphenol compounds, flavonoids and antioxidant compounds that can be obtained by extraction methods. However, with the conventional extraction method it has the disadvantage of long extraction time and requires a lot of solvents. Therefore, this study discusses the use of microwave assisted extraction (MAE) method to extract the leaves of Torbangun. This study uses two treatment factors on MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This suggests that ethanol is more effective in terms of extracting the antioxidant-contributing compounds, such as phenolics and flavonoids, in Torbangun compared to water. Hendrawan et al (2019) used distilled water (aquadest) as the extraction solvent to study the antioxidant activity of dried Torbangun leaves extract using microwave assisted extraction method. In that study, the lowest IC50 value is found at around 9000 ɥg/mL using the highest microwave power (300 watts) and the longest extraction time (3 minutes).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This suggests that ethanol is more effective in terms of extracting the antioxidant-contributing compounds, such as phenolics and flavonoids, in Torbangun compared to water. Hendrawan et al (2019) used distilled water (aquadest) as the extraction solvent to study the antioxidant activity of dried Torbangun leaves extract using microwave assisted extraction method. In that study, the lowest IC50 value is found at around 9000 ɥg/mL using the highest microwave power (300 watts) and the longest extraction time (3 minutes).…”
Section: Antioxidant Activitymentioning
confidence: 99%